2005
DOI: 10.1002/ca.20111
|View full text |Cite
|
Sign up to set email alerts
|

Transverse carpal muscle in association with carpal tunnel syndrome: Report of three cases

Abstract: Anomalous muscles of the upper extremity are common, however, symptomatic anomalies causing CTS are rare. Three cases of CTS that are believed to be caused by an anomalous muscle located palmar to the transverse carpal ligament with transversely oriented muscle bundles is presented. Despite the arguments in literature, this is certainly an anomalous muscle that can be encountered during carpal tunnel release and be problematic to manipulate when minimally invasive approaches are chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
1
19
0
2
Order By: Relevance
“…8 Some also believe that this muscle has a role in the pathogenesis of carpal tunnel syndrome. 5,7 Because of this controversy, the muscle has been named differently by various authors, such as the anomalous origin of thenar/hypothenar muscles, 9 the broad origin of thenar/hypothenar muscles from the TCL, 10 the hypertrophic muscle of the TCL, 11 and musculus transversus carpi. 6 Note that this muscle has no relationship to the palmaris brevis, which is a subcutaneous muscle arising from the ulnar border of the palmar aponeurosis and pisiform, and inserting into ulnar skin and the fascia of hypothenar muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Some also believe that this muscle has a role in the pathogenesis of carpal tunnel syndrome. 5,7 Because of this controversy, the muscle has been named differently by various authors, such as the anomalous origin of thenar/hypothenar muscles, 9 the broad origin of thenar/hypothenar muscles from the TCL, 10 the hypertrophic muscle of the TCL, 11 and musculus transversus carpi. 6 Note that this muscle has no relationship to the palmaris brevis, which is a subcutaneous muscle arising from the ulnar border of the palmar aponeurosis and pisiform, and inserting into ulnar skin and the fascia of hypothenar muscles.…”
mentioning
confidence: 99%
“…[5][6][7][8] Some believe that this is a separate anomalous muscle, 6 whereas others believe it is mostly a hypertrophic thenar muscle origin from the TCL. 8 Some also believe that this muscle has a role in the pathogenesis of carpal tunnel syndrome.…”
mentioning
confidence: 99%
“…Among these variants are Struthers's ligament, aberrant muscles in and around the carpal tunnel, and, of course, LAA itself. [31][32][33][34][35] In most of these reports, the variants are encountered during surgical procedures releasing the nerve from compression. In the present study, however, subjects with LAA were selected from a healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] It has been suggested that these muscles have a role in the etiology of CTS. [1][2][3][4] Division of these muscle fibers has also been implicated in contributing to pillar pain. 8 In addition, the relationship between muscle morphology and motor branch types has been highlighted recently.…”
mentioning
confidence: 99%
“…4 The purpose of this study was to test the hypothesis that division of muscle fibers lying over or within the TCL in an open carpal tunnel release does not have an effect on outcomes in patients with CTS.…”
mentioning
confidence: 99%